Flavor profiling of apple ciders from the UK and Scandinavian region. (March 2018) - Qin, Zihan; Petersen, Mikael A.; Bredie, Wender L.P.
Abstract: The aim of this study was to characterize the flavor profiles of 14 commercial apple ciders from the United Kingdom and Scandinavian region. The flavor properties were established by sensory profiling and analysis of volatile and non-volatile components, including titratable acidity, pH, residual sugars and organic acids. A total of 72 volatile compounds were identified in the 14 apple ciders using dynamic headspace sampling (DHS) coupled to gas chromatography–mass spectrometry (GC/MS). The main volatile compounds found in apple ciders were esters and higher alcohols, followed by aldehydes and fatty acids. Sensory characterizations of the aroma and taste of apple ciders were carried out by a trained sensory panel using descriptive analysis with 23 sensory attributes. The attributes apple, cooked apple, yeasty, sweet and sour were the most predominant sensory descriptors used to describe the similarities and differences in the samples. Principal component analysis (PCA) showed that floral and fruity ( fresh apple, banana and pear ) odors were highly associated with sweet taste and opposed to the more complex aroma attributes ( yeasty, lactic, chemical, mouldy, black pepper and earthy ) and sour taste. Most of the UK apple ciders were characterized by these complex odors and taste notes sour, astringent and bitter, whereas ciders from the Scandinavian region had diverse sensory profiles. Partial least squares regression (PLS) based on the sensory and chemical data was able to cluster the ciders according to differences in production methods (oak-aged or spontaneous fermentation; controlled malolactic fermentation; industrial production with flavor modifications). Moreover, this study also suggested that ciders with marked levels of acetate esters were characterized by cooked/fresh apple, citrus and tropical fruit odors. Graphical abstract: Highlights: Flavor profiles of commercial apple ciders from the UK and Scandinavian region were studied. A group of ciders were clustered according to floral, fruity odors and sweet taste. Ciders from all three countries formed a cluster described by the more complex odors. A third group of ciders with marked levels of acetate esters were characterized with cooked/fresh apple and citrus odors. PLS regression of chemical and sensory data grouped ciders according to differences in production methods.